2002
DOI: 10.1079/phn2002257
|View full text |Cite
|
Sign up to set email alerts
|

Dietary intakes of 6–24-month-old urban South Island New Zealand children in relation to biochemical iron status

Abstract: Objective: To investigate food sources and intakes of iron, and dietary factors associated with serum ferritin levels in 6-24-month-old children. Design: A cross-sectional survey employing proportionate cluster sampling was conducted in 1998/1999. Dietary intakes were assessed using a non-consecutive 3-day weighed food record. Serum ferritin and C-reactive protein were analysed from non-fasting venepuncture blood samples and general sociodemographic data were collected. Setting: Cities of Christchurch, Dunedin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
54
4
2

Year Published

2003
2003
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(71 citation statements)
references
References 27 publications
8
54
4
2
Order By: Relevance
“…Nevertheless, an age-related decline in iron stores in this group of children is consistent with longitudinal and intervention studies, which generally show that ferritin levels decline across the 6-24 month age range when cows' milk or unfortified formula is fed, whereas they remain constant when children consume iron-fortified formula (Fuchs et al, 1993;Michaelsen et al, 1995;Daly et al, 1996;Gill et al, 1997;Oti-Boateng et al, 1998;Morely et al, 1999;Sherriff et al, 1999;Virtanen et al, 2001). It is also consistent with the observed dietary iron intakes in our study which were markedly lower in the 12-24 month than 6-11.9-month-old children (8.4 vs 4.6 mg/day) (Soh et al, 2001). Clearly, there is a need to examine intervention strategies to increase the iron intakes of young New Zealand toddlers to reduce their risks of developing functional iron deficiency.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…Nevertheless, an age-related decline in iron stores in this group of children is consistent with longitudinal and intervention studies, which generally show that ferritin levels decline across the 6-24 month age range when cows' milk or unfortified formula is fed, whereas they remain constant when children consume iron-fortified formula (Fuchs et al, 1993;Michaelsen et al, 1995;Daly et al, 1996;Gill et al, 1997;Oti-Boateng et al, 1998;Morely et al, 1999;Sherriff et al, 1999;Virtanen et al, 2001). It is also consistent with the observed dietary iron intakes in our study which were markedly lower in the 12-24 month than 6-11.9-month-old children (8.4 vs 4.6 mg/day) (Soh et al, 2001). Clearly, there is a need to examine intervention strategies to increase the iron intakes of young New Zealand toddlers to reduce their risks of developing functional iron deficiency.…”
Section: Discussionsupporting
confidence: 90%
“…Likewise, the higher susceptibility of boys to depleted iron stores compared to girls has been partially attributed, by some investigators, to their more rapid growth rate (Male et al, 2001). In our study and others, dietary factors also apparently played an important role in the determination of ferritin levels, particularly the consumption of cows' milk and iron-fortified formulae (Soh et al, 2001). Certainly, dietary factors accounted for the associaIron deficiency in 6-24-month-old New Zealanders P Soh et al tions found between ferritin and the variables of age and weight-for-age percentiles (Table 4 and Soh et al, 2001).…”
Section: Discussionsupporting
confidence: 58%
See 3 more Smart Citations